Policy Implementation Strategy of West Bandung District Health Office in Stunting Intervention During COVID-19 Pandemic - Fitri Aditri; Dian Luthfiana Sufyan; Luh Desi Puspareni (Ikatan Sarjana Gizi Indonesia (ISAGI), 2021)
The government has a target of reducing stunting to 14% by 2024. However, the COVID-19 pandemic has the potential to disrupt the government's focus in reducing stunting, including the West Bandung District Health Office, whose area is the focus location for stunting since 2018. This research aims to explore policy implementation strategies West Bandung District Health Officein stunting intervention during the COVID-19 pandemic. The method used in this research is descriptive qualitative with a case study approach. The research informants were 4 people who were officials in the work area of the West Bandung District Health Office and including the inclusion criteria. Data were collected by in-depth interviews, documentation, and triangulation. After processing and analyzing the data, the following results were obtained: The strategy for implementing the policies of the West Bandung District Health Office in stunting interventions, especially specific nutrition interventions during the COVID-19 pandemic, including through a role-sharing approach, take advantage of digital media, every activity carried out in accordance with COVID-19 health protocols, Holding Integrated Healthcare Center “Sweeping”, using priority strategies to streamline the budget, and synergize the COVID-19 prevention program with stunting.. Despite having a special strategy, the increase in the prevalence of stunting during the COVID-19 pandemic in West Bandung District is unavoidable.